ONDE ESTÃO OS BRANCOS?: Desvelando a branquitude na Arte Brasileira - RAFAEL DANTAS DE OLIVEIRA (2023)
Based on Cultural Studies (Hall, 2013a, 2013b ; Restrepo, 2014), Critical Studies of Whiteness (Bento, 2002, 2022; Cardoso, 2020; Carone, 2014; Schucman, 2020; Sovik, 2004) and Brazilian Art, this dissertation has the general objective of identifying, understanding and analyzing the characteristic and organizational patterns of whiteness in Brazilian Art (Hall, 2013a, 2013b), and based on the Cultural Studies understanding of culture as power and vice versa, in which the general organization is studied In a particular case, I turn to radical contextualism and methodological pluralism in the following way: first, I identify and analyze the social and historical construction of whiteness and its functioning, as well as its self-identification, in which the strategic contradiction of whiteness manifests itself. Then, based on the historiography of Afro-Brazilian art by white authors (Conduru, 2007, 2009; Cunha, 1983; Rodrigues, 1904; Valladares, 2018) and the production of representation in the field of art – based on the idea of “ negative image” (Sovik, 2017) and the concept “objects in a state of exposure” (Simões, 2019), I analyze how whiteness, when producing the Other, produces itself (Carneiro, 2023; Fanon, 2020; Faustino, 2017; Kilomba, 2019), and as a result, I identify, name and conceptualize visual racism. Next, subverting the logic of power of the white gaze (hooks, 2019), I take the critique of whiteness carried out by Afro-Brazilian artists, and revisit the historiography of Brazilian Art by black authors (Amancio, 2021; Munanga, 2018; Nascimento, 2018; Ribeiro, 2020; Simões, 2019) in order to conceptualize white-Brazilian art. Finally, I make some notes about the actions of white subjects, and advocate for the death of whiteness in Brazilian Art (Yancy, 2022).